hMSH2 forms specific mispair-binding complexes with hMSH3 and hMSH6 - Acharya, Samir (The National Academy of Sciences of the USA, 1996)
The genetic and biochemical properties of three human MutS homologues, hMSH2, hMSH3, and hMSH6, have been examined. The full-length hMSH6 cDNA and genomic locus were isolated and characterized, and it was demonstrated that the hMSH6 gene consisted of 10 exons and mapped to chromosome 2p15-16. The hMSH3 cDNA was in some cases found to contain a 27-bp deletion resulting in a loss of nine amino acids, depending on the individual from which the cDNA was isolated. hMSH2, hMSH3, and hMSH6 all showed similar tissue-specific expression patterns. hMSH2 protein formed a complex with both hMSH3 and hMSH6 proteins, similar to protein complexes demonstrated by studies of the Saccharomyces cerevisiae MSH2, MSH3, and MSH6. hMSH2 was also found to form a homomultimer complex, but neither hMSH3 nor hMSH6 appear to interact with themselves or each other. Analysis of the mismatched nucleotide-binding specificity of the hMSH2–hMSH3 and hMSH2–hMSH6 protein complexes showed that they have overlapping but not identical binding specificity. These results help to explain the distribution of mutations in different mismatch-repair genes seen in hereditary nonpolyposis colon cancer.